Social Structural Effects on the Level and Development of the Individual Experience of Anomie in the German Population - Legge, Sandra; Davidov, Eldad; Schmidt, Peter (International Journal of Conflict and Violence (IJCV), 2008)
Can one observe an increasing level of individual lack of orientation because of rapid social change in modern societies? This question is examined using data from a representative longitudinal survey in Germany conducted in 2002–04. The study examines the role of education, age, sex, region (east/west), and political orientation for the explanation of anomia (micro level) and its development. First we present the different sources of anomie in modern societies, based on the theoretical foundations of Durkheim and Merton, and introduce the different definitions of anomia, including our own cognitive version. Then we deduce several hypotheses from the theory, which we test by means of longitudinal data for the period 2002–04 in Germany using the latent growth curve model as our statistical method. The empirical findings show that all the sociodemographic variables, including political orientation, are strong predictors of the initial level of anomia. Regarding the development of anomia (macro level) over time (2002–04), only the region (west) has a significant impact. In particular, the results of a multi-group analysis show that people from West-Germany with a right-wing political orientation become more anomic over this period. The article concludes with some theoretical implications.